2019
DOI: 10.1371/journal.pone.0218601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early specialization in world-ranked swimmers and general patterns to success

Abstract: Objectives The primary goal was to examine the influence of early specialization on the performance of senior elite swimmers. Secondly, to provide information about the influence of swim style, distance, sex, status, country, years of high-level competition (YHLC) and age in swimmer’s performance. Design Data was obtained from International Federation of Swimming (FINA) regarding the participants 2006–2017 of junior and senior World Championships (WCs). The final filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…The strong relationship between the number of years competing in the WC and the position achieved in senior WC races has been reported previously (Allen et al, 2014;Yustres et al, 2017Yustres et al, , 2019. These studies showed that no significant differences were found between years of high-level competition YHLC for swimmers participating in CM Junior prior to their participation in CM Absolute and those directly participating in CM Absolute.…”
Section: Importance Of Experiencesupporting
confidence: 56%
See 4 more Smart Citations
“…The strong relationship between the number of years competing in the WC and the position achieved in senior WC races has been reported previously (Allen et al, 2014;Yustres et al, 2017Yustres et al, , 2019. These studies showed that no significant differences were found between years of high-level competition YHLC for swimmers participating in CM Junior prior to their participation in CM Absolute and those directly participating in CM Absolute.…”
Section: Importance Of Experiencesupporting
confidence: 56%
“…Athlete development has been described in many studies as an ascending scale and predicted improvements have been made using a linear model or pyramid (Barreiros et al, 2014;Green, 2015). Although reaching a final at the junior WC was not related to success in the senior WC (Yustres et al, 2017), participating (without reaching a final) in junior WC has a positive effect on superior performances in subsequent senior WC (Yustres et al, 2019). These results support the idea that swimming success is achieved through a gradual and progressive scale of talent development.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations